1995
DOI: 10.1007/bf02445845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with selenium and vitamin E on certain immunological parameters in rats

Abstract: It is shown that enriching the rat diet with selenium and vitamin E augments the generation of spleen antibody-producing cells and the T-cell blast-transformation response to mitogen. The addition of selenium alone fails to affect the immune reaction; however, the addition of vitamin E alone boosts the T-cell response to mitogen. Dietary supplementation with selenium and/or vitamin E has no marked effect on the function of peritoneal macrophages or on lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…These results suggested that the cDNA encoded a D 12 -fatty acid desaturase that converted oleic acid to LA specifically. This result again reinforced the previous conclusion that D 12 -fatty acid desaturase from filamentous fungi were only able to convert from C18:1 to C18:2. whereas, the recently reported D 12 -fatty acid desaturase from the Saccharomyce kluyveri can convert C16:1 and C18:1 to C16:2 and C18:2 [27]. Athough the reason remain far to be elucidated, the different hydrophobic profile (data not shown) which indicated different transmembrane topology between S. kluyveri D 12 -fatty acid desaturase and filamentous fungi D 12 -fatty acid desaturases may be useful to make this puzzlement clear.…”
Section: Sequence Comparison Of D 12 -Fatty Acid Desaturase Genes Frosupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggested that the cDNA encoded a D 12 -fatty acid desaturase that converted oleic acid to LA specifically. This result again reinforced the previous conclusion that D 12 -fatty acid desaturase from filamentous fungi were only able to convert from C18:1 to C18:2. whereas, the recently reported D 12 -fatty acid desaturase from the Saccharomyce kluyveri can convert C16:1 and C18:1 to C16:2 and C18:2 [27]. Athough the reason remain far to be elucidated, the different hydrophobic profile (data not shown) which indicated different transmembrane topology between S. kluyveri D 12 -fatty acid desaturase and filamentous fungi D 12 -fatty acid desaturases may be useful to make this puzzlement clear.…”
Section: Sequence Comparison Of D 12 -Fatty Acid Desaturase Genes Frosupporting
confidence: 89%
“…Apart from these, it has been increasingly clear that PUFAs play important roles in the control of adipogenesis, cholesterol regulation and immune response [7][8][9]. Very recently, the potential roles of PUFAs in reducing the heart disease and in improving the vision sensitivity and reading ability have been verified [10][11][12][13]. Therefore, the nutritional and pharmaceutical roles of PUFAs have driven people to explore more suitable resources and to study the mechanisms involving their biosynthesis pathways in order to meet the growing market for this product and to explore more unknown functions of the product.…”
Section: Introductionmentioning
confidence: 99%